The Smurfs and the magic flute - Peyo (Peyo. Smurfs graphic novel, 2010)
This graphic novel features the first comics story in which the Smurfs ever appeared. In Medieval times, Johan, a royal page, and his friend Peewit, come upon a magic flute that makes those who listen to it too long dance until they collapse from exhaustion. When a thief steals the magic flute, Johan and Peewit must seek out the makers of the flute, the Smurfs, to make another magic flute to combat the thief.